The relationship between knowledge and the role of husbands with the implementation of endorphin massage for pregnant women in the working area of the umbrella Sekaki Health Center - Rini Hariani Ratih; Siti Maimanah2; Sellia Juwita (LPPM Universitas Abdurrab, 2025)
Background: Human knowledge is based on curiosity, from experience, the role of the husband during pregnancy in dealing with discomfort during pregnancy, namely back pain caused by muscle strain, if not handled properly, can cause difficulty standing, sitting and even moving if the pain has spread to pelvic and lumbar areas, one of the treatments is endorphin massage. Objective: To determine the relationship between knowledge and the role of husbands with the implementation of endorphin massage for pregnant women in the Payung Sekaki Health Center Working Area. Method: This type of research is quantitative research with an analytical design, carried out in the working area of the Sekaki Umbrella Community Health Center in F. The instrument used was a questionnaire. The population in this study was 35 respondents, sampling using non- probability sampling with the accidental sampling method. Data analysis used univariate and bivariate before carrying out the bivariate test using the chi square test. Results: It was found that the majority of respondents had good knowledge totaling 22 respondents (62.9%), playing a good role totaling 22 respondents (62.9%) and implementing massage totaling 30 respondents (85.7%), the results of the Chi-Square test showed the p value <0.05 with a p value of 0.19, indicating that the relationship between knowledge and the implementation of massage is accepted, and the majority played a good role, amounting to 22 respondents (62.9%), obtained by the Chi-Square test results showing a p value of <0.05 with a value of p value 0.38 indicates that the relationship between role and implementation of massage is accepted. Conclusion: There is a relationship between knowledge and the role of husbands with the implementation of endorphin massage for pregnant women in the working area of the Umbrella Sekaki health center. Suggestion: Husbands who have pregnant wives can do endorphin massage to reduce discomfort during pregnancy. Keywords: Knowledge, role, endorphin massage